Elevated Risky Sexual Behaviors Among Sexual Minority Girls: Indirect Risk Pathways Through Peer Victimization and Heavy Drinking. Issue 11 (June 2020) - Dermody, Sarah S.; Friedman, Mark; Chisolm, Deena J.; Burton, Chad M.; Marshal, Michael P.
Sexual minority girls (SMGs), compared with heterosexual females, are more likely to report negative sexual outcomes including earlier age of sexual intercourse debut, more lifetime and recent sexual partners, pregnancy involvement, and sex while intoxicated. Data describing the mechanisms related to these health disparities are limited. The purpose of this study was therefore to longitudinally assess the roles of sexual minority–related peer victimization and heavy episodic drinking (HED) as mediators of the relation between sexual minority status and sexual outcomes. The girls examined in this study were recruited into a longitudinal study of adolescent health from two large, urban adolescent medicine clinics affiliated with academic medical centers. The final sample for this analysis included 79 SMGs and a comparison group of 127 heterosexual girls aged between 14 and 19 years. Mediation models were run in the structural equation modeling framework. Our results provided evidence to support a serial multiple mediation pathway. SMGs were more likely to report sexual minority–related victimization, and sexual minority–related victimization predicted increased HED, which was subsequently found to prospectively predict increased sexual risk behaviors. Taken together, these novel findings indicate that both sexual minority–related victimization and HED may play important roles in explaining disparities in risky sexual behavior among SMGs.